Video Self-Modeling to Treat Aggression in Students Significantly Impacted by Autism Spectrum Disorder. Issue 4 (December 2019) - Sadler, Kate M.
Research suggests that individuals with autism spectrum disorder (ASD) are at risk of exhibiting aggressive behaviors due to deficits in social communication and restricted and repetitive interests. Individuals with greater symptom severity and/or low cognitive abilities are at the greatest risk of developing aggressive behaviors that tend to be resistant to treatment. Additional research to treat persistently high rates of aggressive behaviors in this population is needed. Video self-modeling (VSM) is an evidence-based practice that has proven effective for individuals with ASD. This study implemented a VSM intervention with three middle school children significantly impacted by ASD who displayed aggressive behaviors using single case design with intersubject replication. Findings demonstrated that all three children decreased in aggressive behavior and maintained that decrease postintervention. Further educational implications are addressed on the use of VSM for addressing aggressive behaviors in children significantly impacted by ASD.